Answer:
the first number is 5
the first second is 6
the first number is 1
Explanation:
x - first number
2x - twice the first number
twice the first number exceeds the second number by 4 so:
2x-4 -the second number
y - the third number
the second number is equal to the sum of the first and third numbers:
2x-4 = x + y
x + y = 2x - 4
-x -x
y = x - 4 - the third number
the sum of three numbers:
x + 2x-4 + x-4 = 4x - 8
The sum of three numbers is 12 so:
4x - 8 = 12
+8 +8
4x = 20
÷4 ÷4
x = 5
2x-4 = 2•5 - 4 = 6
x-4 = 5 - 4 = 1
Check:
5+1 = 6
2•5 = 10, 10-4 = 6